Esterification of Monochloroacetic Acid with n-Butanol Catalyzed by SBA-15 Supported Tungstophosphoric Acid - Jianwei, Xue; Chunli, Liu (Asian Journal of Chemistry, 2010)
The esterification reaction of monochloroacetic acid with n-butanol was carried out with heteropoly acid supported on SBA-15 as catalyst to replace mineral liquid acids. The experimental results indicated that heteropoly acid supported on SBA-15 had effective catalytic performance. The effects of various parameters such as mole ratio of acid to alcohol, reaction temperature, catalyst number and time of reaction were investigated. The optimum reaction conditions were as follows: molar ratio of alcohol to acid 1.3:1, temperature 130 ºC, optimum loading amount 23 %, mass ratio of the catalyst used in the reactants 2.0 %, reaction time 5 h, esterification rate above 98 %. The activities of catalyst are stable after catalyst was reused 30 times.